Sexual Violence Against Children and Women: How their Rights Fulfilled? - Cahyaningtyas, Kurnia Galih (Law Research Review Quarterly, 2021)
The implementation of juridical death penalty has been regulated in law no. 2 year 1964; about the procedures of criminal implementation dropped by courts within the General and Military courts. In reality the implementation of law on the implementation of death penalty is still disputed. The debate over the existence and execution of death penalty has been linked to the human right, the effectiveness and the purpose of persecution. Through the constructivism with ontology, epistemology and methodology, it can answer the community’s understanding and philosophical basis of legislation on the implementation of the death penalty, as well as the dynamics of its relation in Riau province Indonesia. This study is expected to contribute the improvement of the deadly criminal code in the future.